Human Marrow Stromal Cells Enhance Connexin43 Gap Junction Intercellular Communication in Cultured Astrocytes - Qi Gao; Mark Katakowski; Xiaoguang Chen; Yi Li; Michael Chopp Ph.D. (Cell Transplantation, 2005)
Human marrow stromal cells (hMSCs) provide functional benefit in rats subjected to stroke. Astrocytes are coupled into a cellular network via gap junction channels, predominantly composed of connexin-43 (Cx43) proteins. Astrocytes are believed to play a vital role in neuroprotection by providing energy substrates to neurons and by regulating the concentrations of K+ and neurotransmitters via gap junctions. We therefore investigated the effect of factors secreted by hMSCs on gap junction intercellular communication (GJIC), expression of Cx43, and phosphorylation of Cx43 in an astrocyte cell culture system. Exposing rat cortical astrocytes to various concentrations of hMSC conditioned medium, we demonstrate that hMSCs produce soluble factors that significantly increase astrocytic GJIC, measured by the scrape-loading dye transfer method. Immunohistochemistry and Western blot showed increased Cx43 expression concomitant with altered GJIC. As the PI3K/Akt signaling pathway has been demonstrated to alter gap junction expression and GJIC, we selectively blocked phosphoinositide 3-kinase (PI3K). Addition of the PI3K inhibitor LY294002 decreased GJIC and Cx43 expression in astrocytes. These inhibitory effects of LY294002 were countered by the addition of hMSC conditioned media. Furthermore, coculturing hMSCs with rat astrocytes increased astrocyte GJIC in a manner dependent upon the hMSC/astrocyte ratio. These findings demonstrate that hMSCs secrete soluble factors that increase GJIC of astrocytes through upregulation of Cx43, and indicate a mechanistic role for PI3K.